AWARENESS REGARDING OBESITY AMONGST GENERAL PHYSICIANS OF KARACHI - Mannan, Fatima; Hasan, Khawaja Zain; Raj, Honey; Zehra, Nosheen; Ali, Mohammad; Haq, Khawaja Saad; Shamsi, Zaid; Irfan, Wasiya (Journal of Ayub Medical College Abbottabad, 2013)
Background: Obesity is considered a disease and one of the fastest growing global threats. In Pakistan General Physicians (GPs) are approached first in case of any disease thus their knowledge and practices regarding obesity are very important to assess. Our objective was to assess the knowledge and practices of GPs regarding obesity and management. Methods: This was a cross-sectional study conducted among GPs of Karachi. 140 GPs from 17 towns of Karachi were selected by convenience sampling. Data was analyzed using SPSS-16. Results: Total 140 GPs with mean age of 46.1±11.1 years were included in the study. Among them 90 (64.3%) were males and 40 (28.3%) were females. Awareness was assessed regarding factors related to obesity and knowledge was compared on basis of qualification and knowledge update. Significant difference was found for insufficient physical activity (p=0.001) and social problems (p=0.02). On the basis of knowledge update, stress and anxiety (p=0.013) were found to be significant. Significant difference was found in readings for BMI (p=0.038) and waist circumference (p=0.000) to label patient obese. Among several lifestyle modifications advised, significant difference was found for increase fibre in diet (p=0.006), low fat intake (p=0.003), low carbohydrate intake (p=0.02). Conclusion: Overall awareness regarding obesity was fair among GPs, while certain gaps were found in criteria for labelling patient obese. Significant difference in knowledge of GPs was found among those GPs who update their knowledge and who did not. Keywords: Obesity, General Physicians, BMI, Karachi